PESAN IKLAN DALAM MEMBANGUN MEREK - Rahmat Saleh (Politeknik Ubaya, 2017)
The world of advertising in the competition to expose a brand at present isvery tough. Therefore, it is necessary to have efforts and strategies to win thecompetition. The advertising message has an important role to build a brand inthat a message consistency will build the customer mind for a brand. This articlewill discuss how the advertising message is managed through consistentactions to be able to build a brand image. The method undertaken in compilingthis scientific article is the observation of bottled tea drink advertising. Therepetitive and continuing message will be a structured pattern to leave amemory in the customer mind in that brand awareness will be stronger in thecustomer memory for a brand which is the capital in building a strong brand.